SOSIALISASI PERKEMBANGAN SOSIAL MEDIA DALAM FENOMENA CYBERCRIME DI MASYARAKAT DESA SELOGUDIG WETAN - Fadel, Moh. (ABDISUCI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The rapid development of social media has transformed the way people communicate and interact, including in rural areas. Social media not only facilitates access to information and communication, but also introduces a number of risks, such as increased cybercrime. As social media users, residents of Selogudig Wetan Village still struggle to understand the types and impacts of cybercrime, such as online fraud, the spread of fake news, and the misuse of personal information, potentially making them victims in their daily digital activities. This community service program is designed to increase awareness and knowledge of Selogudig Wetan Village residents about the development of social media and the dangers of cybercrime that can arise. Adapted methods include outreach through presentations, interactive discussions, and case studies relevant to the village community's situation. A participatory approach is used to ensure that the understanding gained is contextual and practical. The results of this activity demonstrate an increase in community awareness in recognizing various forms of cybercrime and the importance of wise and responsible social media use. People are beginning to realize the importance of maintaining the security of their personal data and being critical of the information they receive. This program is expected to be the first step in building digital literacy among rural communities to create a safer and healthier digital environment.